Concussion in the National Football League: An overview for neurologists - Casson, I. R.; Pellman, E. J.; Viano, D. C. (Physical Medicine & Rehabilitation Clinics of North America, 2009)
The authors' studies have yielded a great deal of data regarding the biomechanics of head injury and the clinical picture of mild traumatic brain injury (MTBI) in the National Football League (NFL). The research has demonstrated the link between the effects of biomechanical forces on the brain and the clinical symptomatology of the concussed players. New insights into the mechanisms of injury are leading to new ways of protecting football players from the effects of MTBI. The clinical data validate the effectiveness of the current NFL physician approach to the evaluation and treatment of the player who sustains MTBI. There are still many more questions to answer and much more knowledge to be gained from continuing research in this area.